2021
DOI: 10.1249/mss.0000000000002673
|View full text |Cite
|
Sign up to set email alerts
|

W′ Recovery Kinetics after Exhaustion: A Two-Phase Exponential Process Influenced by Aerobic Fitness

Abstract: Purpose: The aims of this study were 1) to model the temporal profile of W′ recovery after exhaustion, 2) to estimate the contribution of changing V ˙O2 kinetics to this recovery, and 3) to examine associations with aerobic fitness and muscle fiber type (MFT) distribution. Methods: Twenty-one men (age = 25 ± 2 yr, V ˙O2peak = 54.4 ± 5.3 mL•min −1 •kg −1 ) performed several constant load tests to determine critical power and W′ followed by eight trials to quantify W′ recovery. Each test consisted of two identic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(52 citation statements)
references
References 45 publications
2
50
0
Order By: Relevance
“…The mechanisms, and even the descriptive kinetics, of W' recovery are still to be clarified, but possibly reflect a complex interplay of biochemical pathways, including restoration of blood and muscle oxygen stores, high-energy phosphates, and the ability to proceed with anaerobic glycolysis ( Miura et al, 2000 ; Jones et al, 2010 ; Chidnok et al, 2013 ; Chorley and Lamb, 2020 ). Recent evidence points toward a bi-phasic recovery, enabling rapid recovery of one fraction of W ', followed by a slower recovery of the remaining fraction ( Caen et al, 2021 ). Moreover, a progressive decrease in W' recovery effectiveness during intermittent exercise has recently been suggested, which could account for the decrease in degree of W' expenditure between rounds ( Figure 4 ; Chorley et al, 2019 , 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms, and even the descriptive kinetics, of W' recovery are still to be clarified, but possibly reflect a complex interplay of biochemical pathways, including restoration of blood and muscle oxygen stores, high-energy phosphates, and the ability to proceed with anaerobic glycolysis ( Miura et al, 2000 ; Jones et al, 2010 ; Chidnok et al, 2013 ; Chorley and Lamb, 2020 ). Recent evidence points toward a bi-phasic recovery, enabling rapid recovery of one fraction of W ', followed by a slower recovery of the remaining fraction ( Caen et al, 2021 ). Moreover, a progressive decrease in W' recovery effectiveness during intermittent exercise has recently been suggested, which could account for the decrease in degree of W' expenditure between rounds ( Figure 4 ; Chorley et al, 2019 , 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence points toward a bi-phasic recovery, enabling rapid recovery of one fraction of W', followed by a slower recovery of the remaining fraction (Caen et al, 2021). Moreover, a progressive decrease in W' recovery effectiveness during intermittent exercise has recently been suggested, which could account for the decrease in degree of W' expenditure between rounds (Figure 4; Chorley et al, 2019.…”
Section: Measurementioning
confidence: 98%
“…Likewise, recovery of exercise tolerance after maximal efforts is affected by the relative intensity of exercise during an active recovery period (Chidnok et al, 2012 ). Therefore, a link between training status and faster recovery of both PCr (Takahashi et al, 1995 ; Tomlin and Wenger, 2001 ) and anaerobic work capacity in general (represented by W') (Caen et al, 2021 ) has previously been suggested. Together, this indicates that the high fitness-level of our elite cyclists potentially explains the smaller decreases in anaerobic power compared to untrained men.…”
Section: Discussionmentioning
confidence: 99%
“…Biochemical and physiological evidence now exists for a relatively faster early recovery and slower later recovery than predicted by a simple exponential. 18,19,21,29 From a more practical standpoint, it is necessary to estimate the parameter, τ W′ . The degree to which Equation 321 can be generalized is unknown, but the present evidence is not promising.…”
Section: The W′ Bal Modelsmentioning
confidence: 99%
“…16,17 While the model's assumptions are mathematically plausible (ie, linear discharge and recovery of the W′), the Morton-Billat 16 model oversimplifies a more complex system. In particular, the W′ recovers curvilinearly after both exhaustive steady-state exercise [18][19][20] and during intermittent exercise. [21][22][23][24] This discrepancy is a concern to athletes and their advisors; without an accurate estimation of the recovery rate, it becomes challenging to accurately calculate the amount of W′ remaining at any point in a workout or race simulation.…”
mentioning
confidence: 94%